Adiabatic Processes Contribute to the Rapid Warming of Subpolar North Atlantic During 1993–2010. Issue 4 (28th March 2022) - Wang, Hanshi; Li, Ziguang; Lin, Xiaopei; Zhao, Jian; Wu, Dexing
Abstract: The Subpolar North Atlantic (SPNA) is a region with complex dynamics, and governs the global heat transport by regulating the Atlantic Meridional Overturning Circulation. During 1993–2010, the upper ocean of SPNA has rapidly warmed. Most studies to date focused on the diabatic processes and meridional heat transport leading to this rapid warming, neglecting the role of adiabatic processes and associated heat redistribution. Here, we investigate the ability of adiabatic Rossby wave adjustment to produce this warming event by designed numerical experiments with a set of simple models, including one‐layer model, reduced‐gravity model and two‐layer model. The comparison between these numerical simulations with observations demonstrates that this rapid warming in the western SPNA is partly generated by the wind stress anomalies. The wind stress curl anomalies in the central and eastern of SPNA trigger the topographic and planetary Rossby waves, propagating the downwelling signals along their waveguides to redistribute heat in the upper ocean and warm the Labrador Sea and Irminger Sea with a 4‐ or 7‐year time lag. Hence, the baroclinic mode dominates the magnitude of the adiabatic warming in the SPNA and the topography shapes its spatial pattern. In addition, local and remote wind forcing jointly contributes to this warming. Plain Language Summary: The Subpolar North Atlantic (SPNA) is a key region to influence global climate through modulating the Atlantic Meridional Overturning Circulation (AMOC). There was an abrupt warming in the SPNA during 1993–2010 in the observational data sets. Such warming event has been attributed to anomaly meridional heat transport carried by the AMOC, which is induced by the buoyancy forcing in the SPNA. Here, we designed some numerical experiments with a set of simple ocean models to show the potential role of wind forcing and associated heat redistribution in this warming event. The local and remote wind stress curl anomalies in the central and eastern of the SPNA trigger two types of Rossby waves, propagating the downwelling signals along the waveguides, then redistribute heat in the upper ocean and warm the Labrador Sea and the Irminger Sea. The magnitude of the wind‐forced adiabatic warming in the SPNA is controlled by the ocean's delay response to wind, but its spatial pattern is shaped by the topography. Key Points: The adiabatic processes and associated heat redistribution show a potential role to the rapid warming in the SPNA during 1993–2010 The baroclinic mode dominates the magnitude of the adiabatic warming in the SPNA and the topography shapes its spatial pattern The topographic and planetary Rossby waves triggered by remote wind forcing propagate westward to redistribute heat in the western SPNA